If $A,B$ and $A+B$ are all $n \times n$ invertible matrices. Prove that $(A^{−1})+(B^{−1})$ is equal to $(A+B)^{-1}$

I don't know how to prove that. please help.

  • 13
    $\begingroup$ Usually it's difficult to prove things that are false. $\endgroup$ – Eric Wofsey Sep 10 '18 at 1:34
  • $\begingroup$ You made my day @EricWofsey $\endgroup$ – Ahmad Bazzi Sep 10 '18 at 1:35
  • $\begingroup$ Try to multiply $\,\left(A+B)\cdot(A^{-1}+B^{-1}\right)\,$ and see if you get the identity matrix. $\endgroup$ – dxiv Sep 10 '18 at 1:36
  • 2
    $\begingroup$ You've already received two answers to your question. Don't change your question. Ask a new one. $\endgroup$ – Theoretical Economist Sep 10 '18 at 2:00

Why go to matrices when it doesn't even apply to scalars?

Let $A = 1$ and $B = 2$ so $(A+B)^{-1} = \frac{1}{3}$. BUT $$A^{-1} + B^{-1} = \frac{1}{1} + \frac{1}{2} = \frac{3}{2} \neq (A+B)^{-1} $$

| cite | improve this answer | |

This is wrong. For example: $A=B=\begin{pmatrix}1&0\\0&1\end{pmatrix}$

Then $A^{-1}=B^{-1}=\begin{pmatrix}1&0\\0&1\end{pmatrix}$

But $(A+B)^{-1}=\begin{pmatrix}2&0\\0&2\end{pmatrix}^{-1}=\begin{pmatrix}\frac12&0\\0&\frac12\end{pmatrix}\neq \begin{pmatrix}1&0\\0&1\end{pmatrix}+\begin{pmatrix}1&0\\0&1\end{pmatrix}$

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.